2017
DOI: 10.5194/gmd-10-3821-2017
|View full text |Cite
|
Sign up to set email alerts
|

ORCHILEAK (revision 3875): a new model branch to simulate carbon transfers along the terrestrial–aquatic continuum of the Amazon basin

Abstract: Abstract. Lateral transfer of carbon (C) from terrestrial ecosystems into the inland water network is an important component of the global C cycle, which sustains a large aquatic CO 2 evasion flux fuelled by the decomposition of allochthonous C inputs. Globally, estimates of the total C exports through the terrestrial-aquatic interface range from 1.5 to 2.7 Pg C yr −1 (Cole et al., 2007;Battin et al., 2009;Tranvik et al., 2009), i.e. of the order of 2-5 % of the terrestrial NPP. Earth system models (ESMs) of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 89 publications
(161 reference statements)
2
106
1
Order By: Relevance
“…It could also be due to the high value of DOC input from rainfall, which is not represented in JULES-DOCM (Liu and Sheu, 2003). Recent studies have indicated that including this flux in models can have a significant impact on the DOC in soil (Lauerwald et al, 2017).…”
Section: Measurements Versus Model Simulationsmentioning
confidence: 99%
“…It could also be due to the high value of DOC input from rainfall, which is not represented in JULES-DOCM (Liu and Sheu, 2003). Recent studies have indicated that including this flux in models can have a significant impact on the DOC in soil (Lauerwald et al, 2017).…”
Section: Measurements Versus Model Simulationsmentioning
confidence: 99%
“…For instance, the DOC coming from throughfall is not represented in ORCHIDEE-SOM, although it is a substantial source of soil DOC in tropical ecosystems (Lauerwald et al, 2017). Furthermore, the use of the hydrological module ORC11, which implies free drainage in the bottom layer, currently limits the representation of more humid ecosystems, such as wetlands or peatlands where shallow water tables are present, and needs to be addressed in the near future.…”
Section: Model Limitations and Further Workmentioning
confidence: 99%
“…8). Once the soil module in ORCHIDEE-SOM is optimized for large-scale simulations and linked to the existing DOC river scheme (Lauerwald et al, 2017), it will improve the predictions of SOC vulnerability to climate change and the predictions of the present and future contribution of aquatic continuum fluxes to the global C cycle, thus improving the allocation of terrestrial and ocean C sinks.…”
Section: Model Limitations and Further Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, infiltration of meltwater into frozen soil could be permitted when accounting for sub-grid-scale variability of topsoil freezing and drying which would enhance infiltration (Gray et al, 2001). Other perspectives are the improvement of the floodplain parameterization in ORCHIDEE-MICT (Lauerwald et al, 2017) and the inclusion of natural lakes and artificial reservoirs.…”
Section: River Dischargementioning
confidence: 99%